The history of sustainable development and the impact of the energy system. (4th October 2012) - Schlör, Holger; Fischer, Wolfgang; Hake, Jürgen-Friedrich
This paper describes the origin of the idea, term and concept of sustainable development. Driving forces were fundamental crises, which were essentially crises of the energy system: the idea originated during the crisis of the medieval agrarian solar system; the term emerged when the agrarian energy system could not satisfy the growing energy demand of the emerging industrial age at the end of the 18th century; the concept originated at the end of the 20th century, when the fossil fuel energy system came close to its ecological limits and society was in search of a concept reconciling ecological, economic and social goals for present and future generations. Currently, we are witnessing a slow transition to a new, probably a post-fossil energy system. Therefore, managing the present and future in a sustainable way is a task that will accompany humanity on its way into the future.